Surfactants, its applications and effects on environment - Shah, SK; Bhattarai, A; Chatterjee, SK (BIBECHANA, 2010)
Surfactant is being considered as a very demandable molecule in the field of chemistry. This paper reviews most important factors especially the uses of surfactants and their effects on environment. Evaluation of surfactants are based on examining the ability of the surfactant to maintain lower interfacial tension between target contaminant and water, satisfying lower CMCs, and sustaining lower sorption and precipitation to target substrate. Surfactant mixtures of anionic and nonionic surfactant are shown to be excellent candidates for robust surfactant cleaners. Keywords: Surfactant; Interfacial tension; Critical micelle Concentration; Anionic surfactant; Nonionic surfactant DOI: 10.3126/bibechana.v7i0.4047 BIBECHANA 7 (2011) 61-64